Ґенеза психологічної сутності феномена «соціальний інтелект» - Шпортун, А. М.; Shportun, A. M. (Габітус. - 2024. - Вип. 59. - С. 244-248, 2024)
Стаття присвячена феномену «соціальний інтелект». Наголошено, що розвиток соціального інтелекту має першочергове значення в сучасному суспільстві. Наявна неоднозначність у розумінні його психологічного змісту й компонентів підкреслює необхідність пошуку ефективних методів налагодження спільного функціонування людей у суспільстві та розвитку міжособистісних відносин. Людина з високим рівнем соціального інтелекту здатна ефективно спілкуватися, вирішувати конфлікти, розуміти та приймати критику, а також будувати гарні стосунки з навколишніми. Розвиток цих навичок сприяє успішній соціальній адаптації та інтеграції в суспільне життя. Соціальний інтелект є ключовим елементом для побудови здорових і плідних взаємин між людьми, сприяючи як особистісному, так і професійному розвитку.

The article is devoted to the phenomenon of “social intelligence”. It is emphasized that the development of social intelligence is of paramount importance in modern society. The existing ambiguity in understanding its psychological content and components emphasizes the need to find effective methods for establishing the joint functioning of people in society and the development of interpersonal relations. A person with a high level of social intelligence is able to communicate effectively, resolve conflicts, understand and accept criticism, and build good relationships with others. The development of these skills contributes to successful social adaptation and integration into society. Social intelligence is a key element for building healthy and fruitful relationships between people, contributing to both personal and professional development. It is noted that the term “social intelligence” was first used by the American psychologist and philosopher J. Dewey. However, the scientific popularity of this concept is associated with E. Thorndike, who studied the problem of intelligence, its features, use and measurement. The scientist interpreted social intelligence as the ability to understand and manage people, to act wisely in human relations. With the publication of his work, the phenomenon of social intelligence began to be actively studied. It is emphasized that the construct of the phenomenon of “social intelligence” is quite controversial. The theoretical analysis of the problem of social intelligence indicates the diversity of its interpretations in psychological science, despite almost a century of study. The development of ideas about social intelligencehas changed from considering it as an ability separated from general intelligence to understanding it as a social and cognitive personal characteristic that contributes to a person’s social effectiveness. In the professional context, social intelligence is recognized as key for professionals whose work involves social interaction and communication. This ability is a complex system consisting of cognitive, emotional, and behavioral components that develops over the course of an individual’s life, starting from the moment when a person’s interests begin to intersect with those of their communication partners.

Статья посвящена феномену "социальный интеллект". Отмечено, что развитие социального интеллекта имеет первостепенное значение в современном обществе. Имеющаяся неоднозначность в понимании его психологического содержания и компонентов подчеркивает необходимость поиска эффективных методов налаживания совместного функционирования людей в обществе и развития межличностных отношений. Человек с высоким уровнем социального интеллекта способен эффективно общаться, разрешать конфликты, понимать и принимать критику, а также строить хорошие отношения с окружающими. Развитие этих навыков способствует успешной социальной адаптации и интеграции в общественную жизнь. Социальный интеллект является ключевым элементом для построения здоровых и плодотворных отношений между людьми, способствуя как личному, так и профессиональному развитию.
Genesis of the psychological essence of the phenomenon of “social intelligence”
Keywords: феномен; психологічна сутність; соціальний інтелект; соціальна взаємодія; навички спілкування з людьми; phenomenon; psychological essence; social intelligence; social interaction; communication skills with people; психологическая сущность; социальный интеллект; социальное взаимодействие; навыки общения с людьми